2015
DOI: 10.1155/2015/148501
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Myocardial Deformation in 3 Myocardial Layers in Mice by Speckle Tracking Echocardiography

Abstract: Background. Speckle tracking echocardiography (STE) using dedicated high-resolution ultrasound is a relatively new technique that is useful in assessing myocardial deformation in 3 myocardial layers in small animals. However, comparative studies of STE parameters acquired from murine are limited. Methods. A high-resolution rodent ultrasound machine (VSI Vevo 2100) and a clinically validated ultrasound machine (GE Vivid 7) were used to consecutively acquire echocardiography images from standardized parasternal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 22 publications
(39 reference statements)
0
12
0
Order By: Relevance
“…Speckle tracking was performed with EchoPAC software, which uses the LaGrangian strain approach (23). Global longitudinal strain curves were obtained from each of the 2 standard apical views and 1 parasternal long axis view.…”
Section: Methodsmentioning
confidence: 99%
“…Speckle tracking was performed with EchoPAC software, which uses the LaGrangian strain approach (23). Global longitudinal strain curves were obtained from each of the 2 standard apical views and 1 parasternal long axis view.…”
Section: Methodsmentioning
confidence: 99%
“…[51] We found that RS and RSr had greater variability, which was consistent with previous studies, but the exact reason was uncertain. [52]…”
Section: Discussionmentioning
confidence: 99%
“…In patients with pulmonary hypertension for example, longitudinal strain is segmentally decreased despite normal global RV function [ 18 ]. With respect to animal models the application of 2D-strain is emerging, particularly in the assessment of left ventricular function [ 6 , 19 , 20 ]. However, the application of RV strain to animal models is not previously reported, but as with clinical studies, has major potential in characterizing RV function.…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in ultrasound technology, including 2D speckle tracking or strain, have seen these modalities now being applied to clinical practice [ 5 ]. However the application of 2D-Strain in small animals is emerging, and has been recently reported for left ventricular assessment [ 6 ]. A limitation of transthoracic imaging in small animals is the effect of anatomical artifact from the thoracic cage or liver on image quality.…”
Section: Introductionmentioning
confidence: 99%